2012
DOI: 10.1097/phm.0b013e31823d4ee6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the International Classification of Functioning, Disability, and Health and Quality Criteria for Improving Assistive Technology Service Delivery in Europe

Abstract: More effort should be put into integrating research and resources from European projects into practice. Use of the International Classification of Functioning, Disability, and Health model and terminology may support coordination of service delivery systems. The AT research and practice communities in Europe may be able to learn from developments in North America, while continuing to work together, sharing resources and strategies, and communicating results internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Research and development into models of assistive technology service delivery and application of the International Classification of Functioning have made greater progress outside of Europe [61]. In Australia, Alzheimer's Australia has a library to allow individuals to search online for books and websites on topics such as assistive technologies [121].…”
Section: Leisurementioning
confidence: 99%
“…Research and development into models of assistive technology service delivery and application of the International Classification of Functioning have made greater progress outside of Europe [61]. In Australia, Alzheimer's Australia has a library to allow individuals to search online for books and websites on topics such as assistive technologies [121].…”
Section: Leisurementioning
confidence: 99%
“…It has been shown that patients who feel listened to by their health care professional have better outcomes than those who do not [3,16]. For improving AT service delivery, persons with disability have to be entitled to access AT to facilitate their full and effective participation in society and reasonably expect to be central to the decision-making process of services that provide these technologies [17].…”
Section: Introductionmentioning
confidence: 99%
“…While, longer life spans are generally considered desirable, particularly when healthy years of life are increased, with an aging population and longer life expectancy come an increasing prevalence of chronic diseases and conditions associated with aging [2, 3] that can significantly reduce the quality of life. There is considerable recognition that aging and disability are two arenas that are increasingly viewed as a national and international problem requiring effective, practical, and scalable solutions [4-7]. According to data from the U.S. Census Bureau, approximately 18 percent of Americans have a disability involving an activity limitation, and the incidence of disability increases to 54 percent by age 65[8].…”
Section: Demographics Of Elderly and Aging Manual Wheelchair Usersmentioning
confidence: 99%